К‐carrageenan/Na‐alginate wound dressing with sustainable drug delivery properties. (19th January 2021) - Fahmy, Hesham M.; Aly, Amal A.; Sayed, Shymaa M.; Abou‐Okeil, Ashraf
Abstract : Despite К‐carrageenan (КC) merits as a biopolymer convenient for versatile medical applications, it exhibits limitations in processability and reactivity. To overcome such limitations, КC, in this study, was blended with Na‐alginate (SA) in different weight ratios and cross‐linked with potassium ions. The swelling and gel fraction properties demonstrate that the cross‐linked КC/SA matrix of a ratio of 66.7% is suitable to be applied as a topical wound dressing. Characterization of the prepared КC/SA/K + gel film was performed using scanning electron microscope as well as FTIR. The in vitro release of chloramphenicol as a drug model from the nominated loaded film at pH 4.1 reached a constant value after about 3 hours. To enhance the antibacterial properties of the КC/SA/K + film, silver nanoparticles as bioactive additive were loaded in combination with chloramphenicol, and the antibacterial properties of the loaded film were evaluated, and showed high antibacterial properties against both Gram‐positive and Gram‐negative bacteria.